Kebermasalahan Politik Kekerabatan dan Tantangan Pencapaian Ultimate Goal Otonomi Daerah - Eduardo Edwin Ramda (Ministry of Home Affairs, 2021)
The presence of the phenomenon of kinship politics in the 2020 Simultaneous Regional Head Elections triggers a controversy that revolves around its implementation. The existence of kinship politics is feared to have an impact on efforts to achieve the ultimate goal of regional autonomy, namely public’s welfare and a dignified quality of life. The purpose of this research is to map the potential problems and identify the challenges of achieving the ultimate goal of regional autonomy. This research uses a literature study as an analytical tool to answer the objectives of the study. Discussions about kinship politics in Indonesia present a perceptual dichotomy, where on the one hand this is not a problem when the local leadership of kinship politics is able to bring prosperity together. However, on the other hand, this can become a problem when political actors abuse power that perpetuates the strengthening of the oligarchy and ignores the original goal of decentralization, namely, to bring prosperity and a dignified quality of life. Candidates who are affiliated with kinship politics face a fairly formidable challenge, namely, to strengthen regional competitiveness in a sustainable manner based on the principle of transparency in order to maintain public trust during the COVID-19 pandemic.